Assessment of plasma power deposition on the ITER ICRH antennas. (June 2021) - Brank, M.; Pitts, R.A.; Simič, G.; Lamalle, P.; Kocan, M.; Köchl, F.; Gribov, Y.; Polli, V.; Kos, L.
Highlights: Heat fluxes to ITER ICRH antenna Faraday shield evaluated for Q = 10 burning plasmas. Plasma thermal and radiative photon loads included in full 3D CAD geometry. Mitigated ELM SOL heat flux profile produced using fluid parallel transport model. Impact on heat loads of outward radial plasma shifts ( Δ r ) to improve RF coupling assessed. Field line penetration with increasing  Δ r progressively loads Faraday shield. Δ r up to ~ 8 c m potentially acceptable, maximum shield loads. ~ 2 M W m - 2 . Abstract: Ion cyclotron resonance heating (ICRH) is one of the three additional heating schemes to be deployed on ITER. Its two antenna arrays, installed on the outboard midplane, will deliver 20 MW of RF power in the 40–55 MHz frequency range. The plasma-facing component of the antenna assembly is the Faraday screen, comprising beryllium (Be) tile armoured, actively cooled bars located only ~1 cm radially behind the innermost point of the shaped Be first wall panels (FWPs). As such they are in close proximity to the scrape-off layer (SOL) plasma and it is important to assess the maximum heat loads that the screen bars may experience during high power ITER operation. This paper provides a detailed assessment of these loads using the new 3D field line tracing and power deposition framework SMITER (Kos et al., 2019). The focus is on the H-mode, burning plasma scenario, taking into account both plasma heat loading (including average loading due to mitigated Type I ELMs) and the loads due to photonic impact (assessed with the optical ray-tracing package Raysect (Meakins and Carr, 2017)) from power radiated in the core obtained from integrated JINTRAC simulations. Calculations are also performed to assess the minimum allowed antenna to magnetic separatrix distances, for cases in which closer approach may be required to improve RF coupling.